2022
DOI: 10.31004/obsesi.v6i4.2097
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Flash Card Media To Improve Early Childhood Hijaiyah Letter Recognition

Abstract: This study aims to analyze the effectiveness of Flash Card media to improve early childhood hijaiyah letter recognition conducted at Raudlatul Athfal Al Hanafiah Kotaanyar Probolinggo using qualitative methods of case study types. Participants in this study as many as three people, namely the principal, class A teacher, and class B, were taken with a purposive sampling approach. The results of research on the effectiveness of Flash Card media to improve the introduction of early childhood hijaiyah letters show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
2
0
1
Order By: Relevance
“…The results of the current research are consistent with the results of some studies, including (Abu Jamous & Abdullah, 2009;Hussaini et al, 2016;Habibi, 2017;Tsai, 2018;Farida et al, 2019;Munawaroh, 2022;Aisyah, 2022;Hardiyanti & Herda, 2023) which showed in its results that the educational outcome using flashcards was statistically significant, and recommended using flashcards in presenting vocabulary.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the current research are consistent with the results of some studies, including (Abu Jamous & Abdullah, 2009;Hussaini et al, 2016;Habibi, 2017;Tsai, 2018;Farida et al, 2019;Munawaroh, 2022;Aisyah, 2022;Hardiyanti & Herda, 2023) which showed in its results that the educational outcome using flashcards was statistically significant, and recommended using flashcards in presenting vocabulary.…”
Section: Discussionsupporting
confidence: 91%
“…Maajini (2020) showed the effectiveness of using PowerPoint presentations to teach sight words to children with ASD. Aisyah, Ridwan, Faisol, and Muawanah (2022) showed the effectiveness of using flashcards in improving letter recognition in kindergarten in the English language. Farida, Isrina, and Apsari (2019) showed the effectiveness of using flashcards in improving English language vocabulary for seventh graders, as it found statistically significant differences between the mean scores of pupils in the pre and post-measurements for (vocabulary meanings, spelling aspect, vocabulary use, vocabulary reading) in favor of the post measurement.…”
Section: The Study Problemmentioning
confidence: 99%
“…Media flashcard merupakan media yang sangat efektif dalam memberikan stimulasi membaca permulaan anak usia dini. Beberapa penelitian terdahulu menyebutkan bahwa flashcard merupakan media yang bagus digunakan dalam mengembangkan kemampuan membaca awal khususnya dalam mengenal huruf, karena media ini merupakan media simple, berwarna, dan bergambar, sehingga dapat memikat perhatian anak dan memudahkan anak untuk mengingat symbol huruf dengan bantuan gambar pada flashcard itu sendiri (Aisyah, Ridwan, et al, 2022). Dalam penelitian yang dilakukan oleh Amatiran (2023) menunjukkan hasil penelitian bahwa kegiatan mengenal huruf dengan menggunakan media kartu huruf atau flashcard dapat meningkatkan kemampuan membaca permulaan anak.…”
Section: Media Yang Digunakan Dalam Memberikan Stimulasi Kemampuan Me...unclassified
“…(Setiawan et al, 2020;Heinich et al, 2005). Aisyah et al (2022) define media as anything that conveys information from a source to a receiver. From some of these definitions, it can be concluded that media is a tool used to convey messages in learning.…”
Section: Introductionmentioning
confidence: 99%